End of life decommissioning and recycling of solar panels in the United States. A real options analysis. (2nd January 2021) - Vargas, Carlos; Chesney, Marc
ABSTRACT: Hundreds of thousands of tons of solar panel waste are estimated to be produced yearly in the United States from the year 2035 on, most of which could be recycled. This paper estimates the amount of scrap material to be produced from solar panels decommissioning and determines the optimal date and location to establish either centralized or regional recycling centers to better deal with this issue from the perspective of the U.S. government as potential investor. Solar panel recycling could become a multi-billion USD industry, however, the main challenge today is to keep its overall costs down while allowing for the majority of panels to be recycled. Real Options Analysis is deployed to assess the optimal solution to face this challenge. Determining the optimal location of those facilities is a novel approach. Further applications of the model proposed in this work could scale up this analysis at an international level.